Catalogue and type designations for New Zealand Goniaceritae (Coleoptera: Staphylinidae: Pselaphinae) - Shen, Jia-Wei; Leschen, Richard A. B. (Zootaxa, 2019)
A catalogue for the eight Goniaceritae genera that occur in New Zealand is presented, treating a total of 62 species. Seventeen holotypes are confirmed, 38 lectotypes and 99 paralectotypes are designated herein for all valid species but Eupines acceptus Broun, for which type material was not located. One synonymy is proposed: Anabaxis electrica (King, 1863) (= Rybaxis brevis Oke, 1928). Four species of Eupines known only by females are valid species, but without subgeneric assignment. Images of primary type specimens and their original labels are provided.